Asuhan Keperawatan Resiko Perdarahan Pada Ibu Hamil Dengan Placenta Previa: Studi Kasus - Lailatul Fadliyah; Amellia Mardhika (Surya : Jurnal Media Komunikasi Ilmu Kesehatan, 2021)
Introduction: Placenta previa is a condition where the placenta implants in an abnormal place, namely in the lower uterine segment so that it partially or completely covers the birth canal. This situation can result in bleeding before the fetus is at term and ends with the death of the baby.Objective: This study aims to describe nursing care for the risk of bleeding in pregnant women with placenta previa.Methods: This research uses a case study design. Data collection from assessment to nursing evaluation was carried out in the obsgyn room of RSI Nasrul Ummah Lamongan in November 2019. Clients were hospitalized for a minimum of three days. Data collection techniques using interviews, observation, and documentation. Data analysis was carried out using narrative analysis based on analysis of relevant facts and theories.Results: In the study, two respondents were pregnant with 3rd parity, did not experience bleeding during pregnancy, the results of the ultrasound examination showed that the position of the placenta covered the birth canal. The nursing diagnosis established is the risk of bleeding related to pregnancy complications; placenta previa (D0012). The intervention was education, physical activity limitation, consumption of foods rich in vitamin K, iron. observation of bleeding and vital signs and collaborative for further action. Evaluation 72 hours no bleeding, no signs of anemia. The discussion is expected that nurses provide health education about placenta previa and the risk of bleeding in pregnancy.Conclusion: After implementing nursing for 72 hours there was no bleeding, no signs of anemia. The reference from this research is for nurses to provide health education about the risk of bleeding in pregnant women.Keywords: Risk of Bleeding, Placenta Previa, Pregnancy.